Cytotoxic, proapoptotic and antioxidative potential of flavonoids isolated from propolis against colon (HCT-116) and breast (MDA-MB-231) cancer cell lines - Vukovic, Nenad L.; Obradovic, Ana D.; Vukic, Milena D.; Jovanovic, Danijela; Djurdjevic, Predrag M. (Food research international, 2018)
Isolated and structurally confirmed, eleven flavonoids from propolis were examined for their cytotoxicity toward human colon cancer and human breast cancer cells. Their effect on induction of apoptosis and their antioxidative activities were also evaluated. Six flavonoids induced cytotoxic effects in both cell lines. Luteolin had a marked effect on both cell lines, especially on HCT-116 cells (IC50 72h, 66.86μM). Also, luteolin was observed to have the highest apoptotic potential after 72h treatment of examined cell lines (27.13% and 37.09%, respectively). Myricetin exhibited selective inhibition of cell growth (IC50 114.75μM) and induced apoptosis in MDA-MB-231 cells only. Luteolin and galangin exhibited prooxidative properties 24h after the treatment in HCT-116 cells, while myricetin induced prooxidative effects in MDA-MB-231 cells. On the other hand, selected flavonoids exhibited antioxidative properties 72h after the treatment, decreasing superoxide anion radical and nitrite levels in both cell lines. Cytotoxic and proapoptotic effects on colon and breast cancer cell lines and the influence on their redox status make tested flavonoids good candidates for developing new anticancer drugs. [Display omitted] •Eleven flavonoids were isolated from propolis and their structures were confirmed by 1H and 13C NMR spectroscopy.•Six flavonoids induced cytotoxic effects in HCT-116 and MDA-MB-231 cells.•Galangin, luteolin and myricetin elicited apoptosis in HCT-116 and MDA-MB-231 cells.•Galangin, luteolin and myricetin had antioxidative effect on tested cancer cells, 72h after the treatment.